2011
DOI: 10.5272/jimab.2011172.91
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Latex Gloves – Related Complaints Among Dental Student

Abstract: ABSTRACT:Latex gloves are a frequent cause of complaints in dental staff, which complaints may start during the student education.The aim of the present study was to evaluate the prevalence of latex gloves-related complaints among dental students and to establish the etiology of these problems.Material and Methods: 122 dental students completed a questionnaire. Those with latex glove-related complaints were evaluated for latex sensitivity by assessment of skin prick test and for cell-mediated sensitivity to ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Estudiantes que presentan sintomatología con relación al uso de guantes de látex. En la universidad de Plovdif, Bulgaria, el 8.2 % de los estudiantes de odontología tuvieron molestias en la piel de las manos al usar guantes de látex (Stoeva, 2011); Vangveeravong en Tailandia, igual en el año 2011 reporta una prevalencia del 5%. En Saudi Arabia, se reporta una prevalencia de 12.85% de alergia al látex, de igual manera, en un estudio a estudiantes (Al-aslami et al, 2018).…”
Section: Resultsunclassified
“…Estudiantes que presentan sintomatología con relación al uso de guantes de látex. En la universidad de Plovdif, Bulgaria, el 8.2 % de los estudiantes de odontología tuvieron molestias en la piel de las manos al usar guantes de látex (Stoeva, 2011); Vangveeravong en Tailandia, igual en el año 2011 reporta una prevalencia del 5%. En Saudi Arabia, se reporta una prevalencia de 12.85% de alergia al látex, de igual manera, en un estudio a estudiantes (Al-aslami et al, 2018).…”
Section: Resultsunclassified
“…Results showed that 6.2% of participants tested were positive for Type I latex hypersensitivity. [ 51 52 ] Data from 1996 to 2001 from this ongoing cross-sectional study showed a decline in prevalence from 8.5% to 4.3%. [ 51 ]…”
Section: Latexmentioning
confidence: 99%
“…This decline is related to the use of a better quality of latex gloves with lower allergen content. [ 51 53 55 ] In order to reduce the risk of latex product-associated adverse reactions in both HCWs and patients, federal regulatory agencies such as the Food and Drug Administration (FDA), The National Institute for Occupational Safety and Health (NIOSH), Occupational Safety and Health Administration (OSHA), and the CDC have instituted policies and recommendations regarding appropriate selection of products, work practices to reduce risk, employee education, and the monitoring of allergic symptoms. For example, the FDA requires all medical/dental products and/or devices that contain latex to be clearly labeled “contains latex.” In the newly released Guidelines for Infection Control in Dental Healthcare Settings, 2003, the CDC suggests a number of protocols to decline and manage latex sensitivity and associated adverse reactions in dentistry.…”
Section: Latexmentioning
confidence: 99%
See 1 more Smart Citation